In vivo and In vitro Estimation of Colchicine in Gloriosa superba L. by High Pressure Liquid Chromatography - Ajit Kumar, Renu Sarin*, Anirudha Rishi and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The presence of Colchicine in Gloriosa superba was confirmed by Thin Layer Chromatography (TLC) and High Pressure Liquid Chromatography (HPLC) in which a spot coinciding with the authentic sample of Cochicine in Rf value (Colchicine 0.70) appeared. The maximum amount of Colchicine was found in flower (20.7 mg/gdw) and minimum amount was found in stem (7.4 mg/gdw).The In vitro studies showed the maximum amount of Colchicine in 6 week old cultures (22.6 mg/gdw)) and minimum amount in 2 weeks old cultures (15.3 mg/gdw). Key words: Colchicine, Gloriosa superba, HPLC <div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Laboratory of Bioactive Natural Products, Department of Botany, University of Rajasthan, Jaipur -302004 * Corresponding Author, Email: renusarin@sify.com; Tel: +91-141-2701875, +91-9828070584 Please Cite This Article As: Renu Sarin, Anirudha Rishi and Ajit Kumar. 2010. In vivo and In vitro Estimation of Colchicine in Gloriosa superba L. by High Pressure Liquid Chromatography. J. Exp. Sci. 1(4):1-2. Â 